With or Without Gringos: When Panamanians Talk about the United States and Its Citizens (2022)
eng: In local and informal contexts, Panamanians talk about the power of the United States and describe its citizens in multifaceted and complex terms. In this article I examine those views as they are articulated in informal urban settings in Panama City and in conversa- tions with middle-class Panamanians. My respondents evaluate the US-Panama relationship and discuss individual North Americans with realism, reflecting a graceful but critical spirit of forgiveness toward their more powerful ally. A broader awareness of US colonialism in the past is combined with a pragmatic acknowledgement of opportunities in the present and the desire for a more equal relationship in the future. I argue that the opportunity to voice unreserved opinions about power- ful Others can potentially empower local actors.